2008
DOI: 10.2460/javma.232.4.514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathways for release of Rift Valley fever virus into domestic ruminant livestock, ruminant wildlife, and human populations in the continental United States

Abstract: Domestic ruminant livestock, ruminant wildlife, and people in 14 states (Alabama, California, Florida, Georgia, Maine, Maryland, Massachusetts, Minnesota, New Jersey, New York, Pennsylvania, South Carolina, Texas, and Virginia) appeared to be most vulnerable to exposure to RVFV. Pathways analysis can provide the requisite information needed to construct an effective targeted surveillance plan for RVFV to enable rapid detection and response by animal health and public health officials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 54 publications
0
85
0
Order By: Relevance
“…In addition to California, Texas, New York, and Minnesota, the other states identified by pathways analysis as being at elevated risk for the introduction of RVFV are Alabama, Florida, Georgia, Maine, Maryland, Massachusetts, New Jersey, Pennsylvania, South Carolina, and Virginia (Kasari et al 2008). Evaluation of risk in these states through degree-day analysis is beyond the scope of this project; however, extrapolation from the target states suggest that the southern states (Alabama, Florida, Georgia, Virginia, Maryland, and South Carolina) have moderate levels of risk, as they are warm and have significant but not extremely dense livestock populations.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to California, Texas, New York, and Minnesota, the other states identified by pathways analysis as being at elevated risk for the introduction of RVFV are Alabama, Florida, Georgia, Maine, Maryland, Massachusetts, New Jersey, Pennsylvania, South Carolina, and Virginia (Kasari et al 2008). Evaluation of risk in these states through degree-day analysis is beyond the scope of this project; however, extrapolation from the target states suggest that the southern states (Alabama, Florida, Georgia, Virginia, Maryland, and South Carolina) have moderate levels of risk, as they are warm and have significant but not extremely dense livestock populations.…”
Section: Resultsmentioning
confidence: 98%
“…An exemplar for the potential establishment of RVFV in the US is West Nile virus (WNV), another arbovirus originating in Africa, which arrived in New York in 1999 and spread across North America within just a few years (Enserink 2002). A pathways analysis (Kasari et al 2008) has identified regions of the United States that are most likely to see the introduction of RVFV. The goal of this study is to use GIS and degree-day modeling to identify where and when the virus is likely to disseminate in the US after introduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously [46], RVFV is clearly recognized as a biothreat by The US Commission on the Prevention of Weapons of Mass Destruction (WMD) Proliferation and Terrorism [47] and several risk assessment studies have illustrated the potential spread of RVFV once introduced into Europe or the USA [48][49][50][51][52] (http://ppmq.ars.usda.gov/research/ publications/Publications.htm?seq_no_115=235466&pf=1) (http:// nabc.ksu.edu/assets/uploads/rift_valley_report.pdf). RVFV working groups have produced scientific opinions, threat assessments and recommended action plans (surveillance, diagnostics, vector control), for the management of RVFV including the European Food Safety Authority (EFSA) [48], the Animal and Plant Health Inspection Service (APHIS) Centers for Epidemiology and Animal Health multi-agency and university working group on RVFV (reviewed in Kasari et al [49], the USDA's Agricultural Research Service's (ARS) Arthropod-Borne Animal Diseases Research Laboratory (ABADRL) in collaboration with ARS, Center for Medical, and Veterinary Entomology and the USDA, APHIS.…”
Section: Th Eatmentioning
confidence: 99%
“…Many mosquito species are competent vectors of the virus, including species present in North America (10-13), and stable flies and house flies are potential mechanical vectors (14). The range of competent vectors and susceptible ruminant hosts in the United States might contribute to the rapid spread and establishment of the virus if it were introduced, resulting in a significant threat to the livestock industry and public health (15,16). RVFV has been classified as a category A high-priority pathogen by the National Institute for Allergy and Infectious Diseases and is dual listed as a U.S. Department of Agriculture (USDA) select agent due to the high risk to the U.S. livestock industry (17).…”
mentioning
confidence: 99%